PAROTID SPARING IRRADIATION FOR THE HEAD AND NECK CANCERS - Ali, Nasir; Hameed, Shahid; Shah, Mazhar Ali (Journal of Ayub Medical College Abbottabad, 2002)
Parotid sparing is usually accomplished by irradiating the ipsilateral side of the neck while avoiding the opposite parotid. Tumor site, size, pathology and risk of lymphatic metastases dictate the specific anatomy and the amount of tissue that must be irradiated. It has been shown that approximately two third of the patients receiving radical radiation therapy for head and neck cancer experience weight loss1. The amount of weight loss is maximal at three months after irradiation and recovers slowely thereafter. Weight loss during and immediately after treatment is due to acute mucosal reaction, whereas at three to six months later it is due to xerostomia and its sequelae. The greatest weight loss is experienced by patients whose parotid glands are irradiated during the course of treatment for cancers of the oral cavity and oropharynx. Parotid gland function can be spared with three dimensional treatment planning with unilateral head and neck cancers2. Retrospective analysis of 114 irradiated head and neck cancer patients showed that weight correlated with parotid function3,4. When both parotids were irradiated body weight fell to a nadir of minus 14 %, then gradually rose over the ensuing four years but never fully recovered. When one parotid was irradiated and the opposite was avoided, weight fell to a nadir of minus 4 % of the initial weight, fully recovered with in one year and paralleled the weigh of the controls whose parotids were not irradiated